Insecticide toxicity test by topically processing of insects - Sekun, M.P.; Shevchuk, O.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
A study of the toxicity of insecticides in relation to colorado potato beetle by the method of topically treating of insects was performed. Using the method of probit analysis with the aid of computer program LD50 is the LD95 were determined. The advantages of this method compared to others are described.